Study on China’s manganese resource demand from 2024 to 2035 based on GM-SVR method - Zhao, Xuguang; Han, Xiuli; Feng, Hongye; Liu, Lei; Liu, Qunyi; Liu, Guwang; Du, Baohua; Zhu, Hongjian (Frontiers in Earth Science, 2025)
Manganese is a strategic mineral resource primarily utilized in iron and steel metallurgy. As the world’s largest consumer of manganese, China’s future demand for this resource is crucial for its economic and social development and industrial planning. This paper focuses on manganese demand in China’s iron and steel sector, establishing a combined grey prediction model and support vector regression model (GM-SVR) to forecast China’s crude steel output from 2024 to 2035. Based on this output, we estimate manganese resource demand from 2024 to 2035 using the steel-to-manganese ratio. We employ qualitative and quantitative analyses to project manganese resource needs for this period by applying the “S” shape law and sectoral demand forecasting methods. These three methods indicate a gradual decrease in China’s manganese demand, with projections of 12.86 million tons in 2025, 11.76 million tons in 2030, and 10.64 million tons in 2035. Despite the yearly decline in demand and tightening environmental policies, the overall need for manganese in China remains substantial. Therefore, increasing investment in manganese ore exploration is essential, as well as enhancing research and development in application technologies, optimizing the structure of manganese-related industries, and improving green growth and resource management.